2010
DOI: 10.1375/acri.43.2.282
|View full text |Cite
|
Sign up to set email alerts
|

Maori and Criminal Offending: A Critical Appraisal

Abstract: Since the advent of the Maori renaissance in New Zealand and the shift toward the sociopolitical ideology of biculturalism, the disproportionate representation of Maori in prisons has increased. Criminal justice sector policy asserts that this overrepresentation is best understood as the outcome of Maori experiencing impairments to cultural identity resulting from colonisation. Central to this claim is the notion that ethnicity is a reliable construct by which distinctions can be made between offenders regardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 21 publications
0
20
0
Order By: Relevance
“…Roberts argues that rehabilitation without consideration of an offender's cultural background is senseless. Marie (2010) contended that New Zealand's Department of Corrections' theory of criminal offending by Māori assumes that their overrepresentation in rates of offending, incarceration, and recidivism is a result of Māori "experiencing impairments to cultural identity" as a consequence of colonization (p. 283). This assumption, claims Marie, has led to rehabilitation efforts based on a restoration of cultural identity though there is no evidence to support this theory and such efforts have not shown any noticeable reduction in Māori rates of offending.…”
Section: Literaturementioning
confidence: 99%
See 2 more Smart Citations
“…Roberts argues that rehabilitation without consideration of an offender's cultural background is senseless. Marie (2010) contended that New Zealand's Department of Corrections' theory of criminal offending by Māori assumes that their overrepresentation in rates of offending, incarceration, and recidivism is a result of Māori "experiencing impairments to cultural identity" as a consequence of colonization (p. 283). This assumption, claims Marie, has led to rehabilitation efforts based on a restoration of cultural identity though there is no evidence to support this theory and such efforts have not shown any noticeable reduction in Māori rates of offending.…”
Section: Literaturementioning
confidence: 99%
“…Although Māori make up 14.5% of the total population, they comprise 59% of all female inmates and 51% of all male inmates. It is predicted that the number of Māori in prison will increase given their status as a young population and the fact that criminal offending begins from 12 to 16 years of age (Marie, 2010). A New Zealand Department of Corrections study (2007) found that Māori also have the highest rates of reoffending compared with the total population.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some scholars (e.g. Marie, 2010) argue that there are differential patterns of offending by Māori (the differential involvement thesis). Others contend that practices of direct and indirect discrimination within the CJS are to blame (the discrimination thesis) (Jackson, 1987(Jackson, , 1988Tauri, 2005; see also Workman, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Māori, who are recognised as the indigenous ethnic minority of New Zealand and who constitute around 15% of the nation's population, continue to have poorer outcomes in comparison to their New Zealand counterparts (Bramley et al, 2005). Across numerous indicators, including health (Mason et al, 2012), education (Strategy and System Performance and Ministry of Education, 2008), economic status (Chapple, 2000;Statistics New Zealand, 2007), and criminal justice (Ministry of Justice, 2009;Marie, 2010), Māori are more likely to be disproportionately over-represented in the negative indices when compared to other New Zealanders. Relative to morbidity and mortality data, ethnic surveillance studies indicate that from prenatal development, through infancy and adolescence, and onwards to adulthood and old age, a pattern of diminished health status for Māori not only exists, but persists across the lifespan (Ministry of Health and Statistics New Zealand, 2009;Mason et al, 2012).…”
Section: Introductionmentioning
confidence: 99%